Age of thawed plasma does not affect clinical outcomes or biomarker expression in patients receiving prehospital thawed plasma: a PAMPer secondary analysis. Issue 1 (11th February 2021) - Reitz, Katherine M; Gruen, Danielle S; Guyette, Frances; Brown, Joshua B; Yazer, Mark H; Vodovotz, Yoram; Johanssen, Pär I; Stensballe, Jakob; Daley, Brian; Miller, Richard S; Harbrecht, Brian G; Claridge, Jeffrey; et al.
Abstract : Background: Prehospital plasma administration during air medical transport reduces the endotheliopathy of trauma, circulating pro-inflammatory cytokines, and 30-day mortality among traumatically injured patients at risk of hemorrhagic shock. No clinical data currently exists evaluating the age of thawed plasma and its association with clinical outcomes and biomarker expression post-injury. Methods: We performed a secondary analysis from the prehospital plasma administration randomized controlled trial, PAMPer. We dichotomized the age of thawed plasma creating three groups: standard-care, YOUNG (day 0–1) plasma, and OLD (day 2–5) plasma. We generated HRs and 95% CIs for mortality. Among all patients randomized to plasma, we compared predicted biomarker values at hospital admission (T0) and 24 hours later (T24) controlling for key difference between groups with a multivariable linear regression. Analyses were repeated in a severely injured subgroup. Results: Two hundred and seventy-one patients were randomized to standard-care and 230 to plasma (40% YOUNG, 60% OLD). There were no clinically or statistically significant differences in demographics, injury, admission vital signs, or laboratory values including thromboelastography between YOUNG and OLD. Compared with standard-care, YOUNG (HR 0.66 (95% CI 0.41 to 1.07), p=0.09) and OLD (HR 0.64 (95% CI 0.42 to 0.96), p=0.03) plasma demonstrated reduced 30-day mortality. Among those randomized to plasma, plasma age did not affect mortality (HR 1.04 (95% CI 0.60 to 1.82), p=0.90) and/or adjusted serum markers by plasma age at T0 or T24 (p>0.05). However, among the severely injured subgroup, OLD plasma was significantly associated with increased adjusted inflammatory and decreased adjusted endothelial biomarkers at T0. Discussion: Age of thawed plasma does not result in clinical outcome or biomarker expression differences in the overall PAMPer study cohort. There were biomarker expression differences in those patients with severe injury. Definitive investigation is needed to determine if the age of thawed plasma is associated with biomarker expression and outcome differences following traumatic injury. Level of evidence: II.